Propiedad, planta y equipo (NIC 16) en la Empresa Dismero S.A. de la cuidad de Babahoyo en los periodos 2022-2023. - Figueroa Garces, Doris Gabriela (2024)
This case study entitled "Property, Plant and Equipment (IAS 16) in the Dismero S.A. Company of the city of Babahoyo in the periods 2022-2023", is justified by the importance of guaranteeing transparency and accuracy in the registration of the same. The research is linked to the Financial, Administrative, Tax, Audit and Control management line of research and to the Audit and Control subline. Its general objective is to evaluate the Property, Plant and Equipment (IAS 16) of the Dismero S.A. Company of the City of Babahoyo, in the periods 2022-2023, through the review of the financial statements and as specific objectives to identify deficiencies in internal control, review the depreciation methods applied for PPE and verify the accuracy of the accounting records related to the PPE item during the periods 2022 and 2023. To carry out this case study, a mixed approach was used, since documentary and descriptive research was combined, which allowed quantitative and qualitative research methods, which facilitated the collection of information. The techniques used were observation that was carried out in areas involved in the management of PPE, interviews that were carried out with the accountant, to obtain information on the practices and procedures related to PPE, in addition an Internal Control questionnaire was applied to measure the level of confidence and risk that the company has, an analysis of documents and analysis of financial statements, to make a comparative table between the PPE accounts of the periods studied, to identify variations from one year to the next.